Case Report: Successful treatment of external beam radiation-induced optic papillopathy with intravitreal anti-VEGF - Carey, Andrew R. (Frontiers in Ophthalmology, 2023)
Three cases of optic disc edema from radiation optic neuropathy isolated to the intra-ocular optic nerve following external beam radiation for head and neck squamous cell carcinoma are presented. A literature review of etiology, presentation, and treatment is included for discussion along with proposed diagnostic criteria.